Notch signaling and proneural genes work together to control the neural building blocks for the initial scaffold in the hypothalamus - Ware, Michelle; Hamdi-Rozé, Houda; Dupé, Valérie (Frontiers in Neuroanatomy, 2014)
The vertebrate embryonic prosencephalon gives rise to the hypothalamus, which plays essential roles in sensory information processing as well as control of physiological homeostasis and behaviour. While patterning of the hypothalamus has received much attention, initial neurogenesis in the developing hypothalamus has mostly been neglected. The first differentiating progenitor cells of the hypothalamus will give rise to neurons that form the nucleus of the tract of the postoptic commissure and the nucleus of the mammillotegmental tract. The formation of these neuronal populations has to be highly controlled both spatially and temporally as these tracts will form part of the ventral longitudinal tract and act as a scaffold for later, follower axons. This review will cumulate and summarise the existing data available describing initial neurogenesis in the vertebrate hypothalamus. It has only recently been proposed that loss of Notch signalling in the developing chick embryo causes an increase in the number of neurons in the hypothalamus, highlighting an early function of the Notch pathway during hypothalamus formation. It is well known that the Notch signalling pathway through the inhibition of proneural genes is a key regulator of neurogenesis in the vertebrate central nervous system. Scarce studies have shown genes such as Ascl1 and Hes5 are expressed in the hypothalamus earlier than when the first mature neurons appear. The timing of the transcriptional repressors of the Notch signalling pathway and proneural activators will be analysed. We will discuss novel targets that start to unravel the mechanisms behind neurogenesis in the hypothalamus. Given the critical role that hypothalamic neural circuitry plays in maintaining homeostasis, it is particularly important to establish the targets downstream of this Notch/proneural network.